2017
DOI: 10.1111/appy.12301
|View full text |Cite
|
Sign up to set email alerts
|

A nonpharmacological approach to improve sleep quality in older adults

Abstract: Participation in this community program led to positive effects on sleep disturbances after a year. Psychosocial interventions have potential as a nondrug intervention approach for sleep problems, and further research is needed to understand its mediating mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…Based on previous experience learned in the 2003 SARS epidemic that frontline health professionals were more likely to suffer from psychological problems (2), the authorities in Liaoning province have thus undertaken certain preventive interventions to relieve stress among frontline health professionals, such as timely provision of financial and material supports, mass education on pressure control, online psychological counseling service (e.g., 24-h hotlines), and on-site psychological guidance. These measures could reduce the risk of poor sleep quality (34).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous experience learned in the 2003 SARS epidemic that frontline health professionals were more likely to suffer from psychological problems (2), the authorities in Liaoning province have thus undertaken certain preventive interventions to relieve stress among frontline health professionals, such as timely provision of financial and material supports, mass education on pressure control, online psychological counseling service (e.g., 24-h hotlines), and on-site psychological guidance. These measures could reduce the risk of poor sleep quality (34).…”
Section: Discussionmentioning
confidence: 99%
“…Art was also found to be related to sleep quality (Rawtaer, Mahendran, Chan, Lei, & Kua, ) and decrease distress symptoms and improve health‐related quality of life (Monti et al, ). A previous study indicated that diet preparation and technology‐related activities require a higher level of concentration and increased physical and mental activity in elderly populations.…”
Section: Discussionmentioning
confidence: 99%
“…Art was also found to be related to sleep quality (Rawtaer, Mahendran, Chan, Lei, & Kua, 2017) and decrease distress symptoms and improve health-related quality of life (Monti et al, 2006).…”
Section: Types Of CCC Activities and Outcomementioning
confidence: 99%
“…One study showed that the quality of sleep increased in the elderly living in nursing homes after a 12-week course of reminiscence therapy (22). The results of another study reported that non pharmacological methods such as reminiscence therapy can significantly reduce the sleep disorders in older adults (41). Group reminiscence therapy has a significant positive impact on mental health and its dimensions such as insomnia and anxiety, social dysfunction and depression in elderly population (30).…”
Section: Discussionmentioning
confidence: 99%